(untitled) (Journal on studies and research of academic knowledge, 2018)
In the district of San Pedro del Paraná, Itapúa, an experiment was developed with the objective of evaluating the productive behavior of onion at different doses of N and K with irrigation and omission of irrigation in direct sowing. The design was randomized complete blocks in divided plots, the main plot being the irrigated and non-irrigated plots and the subplots the combination of nitrogen and potassium levels in kg/ha: 50, 100 and 150 N and 75, 150 and 225 K2O, totaling 9 treatments plus one control and four repetitions. Agronomic variables and yields were measured. The application of doses of nitrogen and potassium influenced the productive behavior of the crop, as well as the continuous provision of water through drip irrigation. The 50/75 kg/ha dose of N/K led to higher yields than the control by 27%; greater weight of bulbs of diameter class IV (> 70-90 mm) and reduction of the production of bulbs refug or class <I (<35 mm). The plants submitted to irrigation had yields higher than 29% in comparison to hose not irrigated; as well as obtaining 33% more bulbs of class III (>50-70mm) of greater commercial value.